2022
DOI: 10.1097/cm9.0000000000002008
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori may participate in the development of inflammatory bowel disease by modulating the intestinal microbiota

Abstract: Inflammatory bowel disease (IBD) is a non-specific inflammatory disease of the gastrointestinal (GI) tract that is generally accepted to be closely related to intestinal dysbiosis in the host. GI infections contribute a key role in the pathogenesis of IBD; however, although the results of recent clinical studies have revealed an inverse correlation between Helicobacter pylori (H. pylori) infection and IBD, the exact mechanism underlying the development of IBD remains unclear. H. pylori, as a star microorganism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The relative abundance of Proteobacteria phylum and Firmicutes: Bacteroidetes ratio was related to the stability of microbial community, pro‐inflammatory response, and energy metabolism, which played an important role on maintaining gut microbial homeostasis, 50 the expansion of Proteobacteria was concluded to be a potential marker for unstable microbial community and some metabolic and immune disease in a review, 51 increased value of Firmicutes/Bacteroidetes was found in animal models of NAFLD, 52 but their role on maintaining stomach microbial homeostasis remained unknown. In our study, the abundance of Proteobacteria and Firmicutes: Bacteroidetes ratio declined significantly in H. pylori ‐infected patients, which may illustrate the protective effect of H. pylori on inflammatory bowel disease and child asthma 53‐55 . Firmicutes:Bacteroidetes ratio might be a potential marker for inflammation of gastric mucous, increased value of Firmicutes/Bacteroidetes may represent a higher risk of oncogenesis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The relative abundance of Proteobacteria phylum and Firmicutes: Bacteroidetes ratio was related to the stability of microbial community, pro‐inflammatory response, and energy metabolism, which played an important role on maintaining gut microbial homeostasis, 50 the expansion of Proteobacteria was concluded to be a potential marker for unstable microbial community and some metabolic and immune disease in a review, 51 increased value of Firmicutes/Bacteroidetes was found in animal models of NAFLD, 52 but their role on maintaining stomach microbial homeostasis remained unknown. In our study, the abundance of Proteobacteria and Firmicutes: Bacteroidetes ratio declined significantly in H. pylori ‐infected patients, which may illustrate the protective effect of H. pylori on inflammatory bowel disease and child asthma 53‐55 . Firmicutes:Bacteroidetes ratio might be a potential marker for inflammation of gastric mucous, increased value of Firmicutes/Bacteroidetes may represent a higher risk of oncogenesis.…”
Section: Discussionsupporting
confidence: 56%
“…In our study, the abundance of Proteobacteria and Firmicutes: Bacteroidetes ratio declined significantly in H. pylori-infected patients, which may illustrate the protective effect of H. pylori on inflammatory bowel disease and child asthma. [53][54][55] Firmicutes:Bacteroidetes ratio might be a potential marker for inflammation of gastric mucous, increased value of Firmicutes/Bacteroidetes may represent a higher risk of oncogenesis. The infection of H. pylori may be a result of individual gastric flora disturbance, such as the imbalance of Firmicutes and Bacteroidetes.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that H. pylori , along with inhibited tight proteins and activated mesenchymal-related biomarkers, contributes to gut permeability in chronic AD-related metabolic dysfunction. Although H. pylori is commonly found in the gastric area with acid environment, a recent study has demonstrated that H. pylori may participate in the development of inflammatory disease through regulating of the intestinal microbiota . For instance, H. pylori infection causes small intestinal bacterial overgrowth and increases gastric acid secretion; meanwhile, H. pylori infection is observed in the stomach and the proximal duodenum and the small and large intestines .…”
Section: Resultsmentioning
confidence: 99%
“…Although H. pylori is commonly found in the gastric area with acid environment, a recent study has demonstrated that H. pylori may participate in the development of inflammatory disease through regulating of the intestinal microbiota. 55 For instance, H. pylori infection causes small intestinal bacterial overgrowth and increases gastric acid secretion; meanwhile, H. pylori infection is observed in the stomach and the proximal duodenum and the small and large intestines. 56 It has been found that H. pylori infection is a risk factor for small intestinal ulcerative lesions.…”
Section: H Pylori In the Gutmentioning
confidence: 99%
“…Disordered intestinal microbiota is the underlying pathogenic mechanism of IBD ( 28 30 ). To investigate whether intestinal flora is involved in H. pylori -alleviated colitis, we collected stool samples from these mice and subjected them to high-throughput shotgun metagenomic sequencing to profile their microbial community taxonomic composition.…”
Section: Resultsmentioning
confidence: 99%